PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH REVALUASI ASET TETAP DI INDONESIA (Studi Empiris pada Perusahaan yang Tercatat di Bursa Efek Indonesia 1998-2007) - , DWI ARI KURNIAWATI, Irfan Nursasmito, S.E., M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study attempts to compare the company's financial performance before and after the revaluation of fixed assets. Comparable financial performance are the stock price, and profitability ratios include return on assets (ROA) and return on equity (ROE). This study aimed to see whether there are differences in the stock price, ROA, and ROE before and after the revaluation of fixed assets. The sample used in this study are listed companies in Indonesia Stock Exchange from 1998 to 2007 were revalued fixed asets (upward revaluation). This study using a non-parametric analysis (Wilcoxon signed ranks test). Non-parametric analysis is used becaue data of third variables, both stock prices, ROA, and ROE are not normally distributed. Based on the results of testing the first hypothesis, it was found the difference in the stock price one year before and one year after the revaluation of fixed assets. However, this study failed to prove the existence of differences in ROA and ROE before and after the revaluation of fixed assets.